2019
DOI: 10.1634/theoncologist.2019-0492
|View full text |Cite
|
Sign up to set email alerts
|

Regorafenib in Combination with First-Line Chemotherapy for Metastatic Esophagogastric Cancer

Abstract: Background Angiogenesis is critical to gastroesophageal adenocarcinoma growth and metastasis. Regorafenib is a multikinase inhibitor targeting angiogenic and stromal receptor tyrosine kinases. We evaluated whether regorafenib augments the antitumor effect of first‐line chemotherapy in metastatic esophagogastric cancer. Materials and Methods Patients with previously untreated metastatic gastroesophageal adenocarcinoma received 5‐fluorouracil, leucovorin, and oxaliplatin (mFOLFOX6) every 14 days and regorafenib … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In the past 3 years, lots of studies have focused on the antiproliferation and antiapoptosis of regorafenib in HCC cells, and its mechanisms involve in the inhibition of ERK/nuclear factor kappa B activation, Bcl‐xL/Mcl‐1 ratio, and Cyclin E1/Mcl‐1 signaling pathway, and so forth 30–32 . Importantly, regorafenib was approved for refractory mCRC in 2013, and a number of recent clinical trials for regorafenib were carried out in metastatic malignancies 11–13 . Nonetheless, the role of regorafenib in HCC metastasis and related mechanisms are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the past 3 years, lots of studies have focused on the antiproliferation and antiapoptosis of regorafenib in HCC cells, and its mechanisms involve in the inhibition of ERK/nuclear factor kappa B activation, Bcl‐xL/Mcl‐1 ratio, and Cyclin E1/Mcl‐1 signaling pathway, and so forth 30–32 . Importantly, regorafenib was approved for refractory mCRC in 2013, and a number of recent clinical trials for regorafenib were carried out in metastatic malignancies 11–13 . Nonetheless, the role of regorafenib in HCC metastasis and related mechanisms are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Importantly, regorafenib was approved for refractory mCRC in 2013, and a number of recent clinical trials for regorafenib were carried out in metastatic malignancies. [11][12][13] Nonetheless, the role of regorafenib in HCC metastasis and related mechanisms are still unclear. In the present study, we found that regorafenib effectively refrained VM formation, migration, and invasion in HCC cells.…”
Section: Regorafenib Suppresses Tumor Growth and Vm Formation In Pdmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that while the drug was safe to give with the FOLFOX regimen, there was no benefit to the PFS in this cohort. 76 There are several clinical trials underway testing the efficacy of this drug in combination with other chemotherapies for gastric cancer (NCT03722108, NCT02406170, and NCT03627728) Several other trials using antiangiogenic therapy were less successful in GC. The AVAGAST and AVATAR trials showed no additional benefit to OS with bevacizumab (anti-VEGF antibody) added to standard of care.…”
Section: Angiogenesismentioning
confidence: 99%
“…Studies evaluating regorafenib combined with chemotherapy in other settings have produced varied results. A phase 1, doseescalation study in pretreated patients with metastatic esophageal/GC showed promising effects on survival with regorafenib combined with paclitaxel [59], while a phase 2 study of regorafenib combined with FOLFOX failed to meet the prespecified endpoint of 6-month PFS [60]. Several other novel targeted therapies have been evaluated in clinical studies, but only trastuzumab and ramucirumab ( ± paclitaxel) have demonstrated an OS benefit in the first-and second-line setting, respectively [61,62].…”
Section: Gastroesophageal Cancermentioning
confidence: 99%